Number sense profile of prospective elementary school teachers in blended Mathematics learning - Welly Novitasari; Herwin Herwin; Supartinah Supartinah; Putri Wulandari; Budiharti Budiharti (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2024)
Number sense is a skill that contributes significantly to learning mathematics. However, number sense is often positioned as a fundamental skill whose development is more focused on children. The contribution of number sense in mathematics is even more apparent at higher levels of education. Ironically, number sense seems ignored and has become a rarely studied topic in higher education. Thus, the student's number sense ability profile seems buried with various problems. This study aims to reveal the profile of prospective elementary school teachers' number sense abilities and the factors causing their failure in solving math problems during the implementation of blended learning. This study uses a qualitative approach with 37 prospective elementary school teachers as research subjects. The observation of the test and lecture activities is the data collection method. The results showed that the prospective elementary school teachers' number sense ability was still relatively low. Based on the components, the order of number sense abilities is from the highest, namely: (1) knowledge and number facilities with the achievement of 14.41%; (2) knowledge and facilities for number operations with the achievement of 8.12%; and (3) knowledge and facilities of numbers and operations for computing settings with an achievement of 1.8%. The low number sense ability is caused by the habit of solving problems procedurally and the failure to solve problems due to misconceptions, not understanding concepts, inaccuracy, inability to understand questions, and difficulty representing fractions. Various factors causing the failure arose due to the limitations of implementing blended learning.